Interface-induced terahertz persistent photoconductance in rGO-gelatin flexible films. Issue 2 (12th December 2016) - Qi, M.; Zhou, Y.; Huang, Y.; Zhu, L.; Xu, X.; Ren, Z.; Bai, J.
Abstract : Light-induced difference terahertz (THz) spectroscopy is used to investigate the dielectric characteristics of reduced graphene oxide-gelatin (rGO-Gel) flexible films. Abstract : Light-induced difference terahertz (THz) spectroscopy is used to investigate the dielectric characteristics of reduced graphene oxide-gelatin (rGO-Gel) flexible films. RGO-Gel films are observed to exhibit positive photoconductance under 800 nm laser illumination, resulting in the modulation depth of the THz transmission up to 33.5%. Moreover, persistent photoconductance (PPC), which is a prolonged light-induced conducting behavior, has been observed to last as long as tens of seconds in rGO-Gel films. The PPC phenomenon is due to the electrons trapped in the defects of rGO and in the interface between rGO and gelatin, and is enhanced by the strong interaction between rGO (a p-type semiconductor) and gelatin (electron donors). This work holds potential for creating optoelectronic devices based on rGO-Gel films, such as optical modulators, switches, photodetectors, photosensors, and persistent photonic memory devices in the THz region.